2013
DOI: 10.1021/ma4020802
|View full text |Cite
|
Sign up to set email alerts
|

Floated Lamella Films of Styrenic Block Copolymers: Local Shearing Deformations and Heterogeneous Layer at the Substrate

Abstract: We examined the free surface as well as the substrate−film interface of thermally equilibrated block copolymer films forming stacks of glassy−rubbery lamellae and having quantized film thickness due to terrace formation. Upon reversing onto a new substrate, ∼100 nm thick floated films deform without loss of the film integrity, so that the characteristic macroscale topographic pattern is transmitted to the newly formed free surface. The adhesion-driven deformation is attributed to a local shear of the step regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
(87 reference statements)
1
3
0
Order By: Relevance
“…The value of the step height of (12 ± 1) nm (measured with SFM on dried films) multiplied by a degree of swelling of 1.5 indicates a step height in a swollen state of ≈20 nm, corresponding to a half lamella spacing. This result suggests that the wetting conditions are changed by the presence of GNPs, and a heterogeneous lamella sheet from PS and P2VP blocks can be formed at the substrate . This observation is in agreement with earlier work of Lin et al who showed that preferential alignment of nanoparticles close to the substrate may lead to lower surface selectivity, comparable to creation of neutral surfaces by polymer brushes .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The value of the step height of (12 ± 1) nm (measured with SFM on dried films) multiplied by a degree of swelling of 1.5 indicates a step height in a swollen state of ≈20 nm, corresponding to a half lamella spacing. This result suggests that the wetting conditions are changed by the presence of GNPs, and a heterogeneous lamella sheet from PS and P2VP blocks can be formed at the substrate . This observation is in agreement with earlier work of Lin et al who showed that preferential alignment of nanoparticles close to the substrate may lead to lower surface selectivity, comparable to creation of neutral surfaces by polymer brushes .…”
Section: Discussionsupporting
confidence: 91%
“…In ≈40 nm thick PS‐ b ‐P2VP films, a single lamella layer can be stabilized by symmetric wetting conditions, implying that the PS block segregates also to the substrate, or a heterogeneous layer is formed at the substrate . This would be promoted by using substrates which were previously modified by random copolymer brushes to create neutral polymer interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Since the height of corrugation (of order of 100 nm) is significantly smaller that the period of the corrugations (of order of 2000 nm), the substrate topography can be considered as macroscopically smooth, resulting in a homogeneous adhesion of the film to the corrugated support. The adhesion behavior of floated block copolymer films has been earlier addressed in detail . To equilibrate the microphase-separated structures, films have been thermally annealed under vacuum at 120 °C for 18 h.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The adhesion behavior of floated block copolymer films has been earlier addressed in detail. 53 To equilibrate the microphaseseparated structures, films have been thermally annealed under vacuum at 120 °C for 18 h.…”
Section: Methodsmentioning
confidence: 99%